Development of a Novel Methotrexate-Loaded Nanoemulsion for Rheumatoid Arthritis Treatment with Site-Specific Targeting Subcutaneous Delivery - Parvathy Suresh; Mounir M. Salem-Bekhit; Hafsa Palathum Veedu; Sultan Alshehri; Sreeja Chandrasekhar Nair; Sarah I. Bukhari; Vidya Viswanad; Ehab I. Taha; Ram Kumar Sahu; Mohammed M. Ghoneim; Ibrahim Elbagory (Nanomaterials, 2022)
Rheumatoid arthritis (RA) is a systemic, chronic autoimmune disease that causes disability due to progressive inflammation and destruction of the tissues around the joints. Methotrexate is mainly used to prevent the progression of joint destruction and reduce the deformity. The major challenge in treating RA with methotrexate is the systemic side effects that limit dose escalation. Hence, a novel formulation of a methotrexate-loaded nanoemulsion for subcutaneous administration was developed that aims to deliver methotrexate into the system via the lymph. The methotrexate-loaded nanoemulsion was prepared by using the aqueous-titration method. The prepared nanoemulsion was investigated for particle size, surface charge, surface morphology, entrapment efficiency, DSC (differential scanning colorimetry), drug release, hemocompatibility assay, and cytotoxicity, as well as anti-arthritic and stability studies. The vesicle size, zeta potential, PDI (polydispersity index), and entrapment efficiency of the optimized nanoemulsion were 87.89 ± 2.86 nm, 35.9 ± 0.73 mV, 0.27, and 87 ± 0.25%, respectively. The DSC study showed that the crystalline methotrexate was converted to an amorphous form and the drug was fully incorporated into the vesicles. After 72 h, the optimized nanoemulsion showed a drug release of 96.77 ± 0.63%, indicating a sustained-release dosage form. Cytocompatibility testing by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide) assay on macrophage cell lines showed that the nanoemulsion was non-toxic. The formulation showed significant anti-arthritic activity compared to the marketed drug solution. In addition, the nanoemulsion containing methotrexate remained stable for three months when stored at a low temperature. Since the nanoemulsion containing methotrexate has excellent physicochemical properties and lowers systemic side effects by targeted delivery, it is a desirable technology for subcutaneous drug delivery.